Performance of transcatheter pacing system use in Relation to Patient Age. (14th October 2021) - Nicosia, A; Iacopino, S; Nigro, G; Zucchelli, G; Tomasi, L; D'Agostino, C; Ziacchi, M; Piacenti, M; De Filippo, P; Sgarito, G; Foti, R; Campisi, G; et al.
Abstract: Background: Real-world safety data on the use of transcatheter pacing systems in particularly young and elderly patients is still limited. Purpose: The aim of this analysis was to investigate the effect of age on the safety and efficacy of leadless pacemaker implant. Methods: From May 2016 through July 2019, 577 patients were implanted with a leadless single chamber pacemaker according to current pacing indication in 15 Italian cardiologic centers. The population was divided into age quartiles for evaluation, including: 1) <70 years, 2) 70–77 years, 3) 78–83 years, and 4) ≥83 years. Procedural data, complications, electrical parameters were collected at baseline and during the follow up. Results: Procedural-related complication occurrence was very low (<1.0%) and similar in the four subgroups according to age. No cardiac tamponade was reported. Among the groups, no difference was observed in procedural time, fluoroscopy time duration and electrical parameters (mean pacing impedance: 750±192 and 599±156, mean pacing threshold: 0.7±0.5 and 0.7±0.6, and mean right ventricular sensing 10.7±6.1 and 11.5±4.8 at implant and last follow up, respectively). Figure 1 showed the distribution of age in the patient population. Conclusion: The reported data demonstrated a high degree of safety during leadless implant across all patient ages. Procedural complications and device electrical measurements were similar among the different ages. Funding Acknowledgement: Type of funding sources: None.